Hard knocks - Carr, Howie (New York : Forge, 2012)
After the murder of a client, former Boston cop-turned-private investigator Jack Reilly is compelled to sift through decades of corruption to discover who is trying to kill him.
"A Tom Doherty Associates book.&quot
Keywords: Private investigators -- Massachusetts -- Boston -- Fiction; Murder -- Investigation -- Fiction; Corruption investigation -- Fiction; Boston (Mass.) -- Fiction; Mystery fiction